Physical activity in women after mastectomy - Karczmarek-Borowska, Bożenna; Czaja, Ewelina; Golon, Kamila (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Physical activity is very important in course of treatment as well as prognosis of patients with breast cancer and can prevent complications and help to improve the quality of life. The study was conducted in the Amazon Club in Mielec. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and method. The study included 60 women aged 30 up to 68 (mean age 53.6 years). It was conducted by means of the author’s questionnaire and the International Physical Activity Questionnaire (IPAQ). The largest group among the respondents were women over 50 years of age (58.3%). The majority of the study group 58.3% were married women. 70% of the subjects were the residents of the city. The smallest group consisted of women with primary education - 15%, and most were women with secondary education (58.3%). 56.7% of the study group were women not professionally active. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Thanks to physical activity 76.7% of the respondents felt better, also 55% of the women noticed more energy and better wellbeing. A half of the respondents believed that physical activity is important in preventing breast cancer and other cancers. According to a large number of the respondents, physical activity really facilitated their regaining of health after surgery. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. The study showed that younger women (under 50 years) were more active. The women living in rural areas presented slightly higher mean general activity level. The average professional activity of the respondents increased with increasing level of their education. Mean activity of the subjects in terms of movement was the greatest among women with secondary education, slightly less among women with higher education and the smallest among women with primary education.